Study on Measuring and Evaluating the Synergy Effect of Regional Coal Mine Emergency Management in China Based on the Composite System Synergy Model. (19th May 2022) - Hao, Yu; Sun, Chaolun; Wei, Jianping; Gu, Sasa
Abstract : Emergency management of coal mines requires enhanced synergy among departments, institutions, and enterprises, which means overall efficiency in management. In this study, a regional coal mine emergency (CME) management synergy system was established; the synergy theory was adopted to construct the order parameter index system of the regional CME management synergy subsystems. Moreover, the order degrees and synergistic degrees of the regional CME management synergy subsystems in Henan Province, China, in the period 2015-2019 were quantitatively measured and analyzed using the composite system synergy model. The results show that the order degrees of regional CME management synergy subsystems and the synergistic degree of the composite system increase overall during the inspection period. With the gradual formation of the regional CME management synergy mechanism, this period has witnessed a steady improvement in both the synergy value and the considerable synergistic effect.